Perlindungan Hukum terhadap Pemberi Pinjaman Peer to Peer Lending Atas Risiko Kerugian - Devira Andriani; Rasji (Syntax Literate, 2023)
The digital world is experiencing very rapid development and has a lot of influence in various sectors, one of which is the presence of information technology-based lending and borrowing services, namely Peer to Peer Lending. However, it is possible that the implementation of Peer to Peer Lending is at risk of a legal problem, namely default from the Borrower which will harm the Lender who funds the loan application on the Operator's platform. In this regard, this study further aims to find out and analyze the legal protection for lenders related to the risk of default in peer to peer lending-based loan services. In addition, this study also aims to explain dispute resolution due to default in peer to peer lending. The research method used in this study is normative legal research method. Legal protection for lenders with the establishment of special regulations that provide protection for users of Peer to Peer Lending services, namely the Financial Services Authority Regulation Number 77 / POJK.01 / 2016, especially Article 37 and sanctions such as fines, imprisonment, and other additional penalties given after a dispute occurs. Dispute resolution due to default in P2PL can be done outside or inside the court in accordance with the provisions of Article 39 paragraph (1) POJK Number 1 / POJK.07 / 2013.